Pondok Belajar Berbasis Komunitas untuk Peningkatan Literasi dan Numerasi Anak: Program Pendampingan Belajar Pada Anak di Wilayah Tosaren - nur aulia rahmawati; Aldo Aditya Saputra; Elok Ayuandita; Tyas Ayu Putri Fitria; Novia Rosyidatud Dalalah; Ardaraya; Novia Oktarisa Sangganengrum; Ahmad Abdurrois; Riniati; Patrick Nuno; Delvira Listya Putri; Vinna Nur Hamidah; Melia Agustina; Eko Sri Wulaningtyas (PT. Penerbit Riset Sadwa, 2026)
Strengthening children’s literacy and numeracy skills in community settings still faces various challenges, including limited access to non-formal learning assistance, low learning motivation, and inadequate learning support, particularly for children who have dropped out of school. This community service activity aimed to improve children’s literacy and numeracy skills through the establishment of a community-based learning center in Tosaren Village. The program was implemented using a learning assistance approach, which included forming study groups, assigning tutors from community service students, conducting regular learning sessions, and evaluating outcomes through pretests and posttests. The results indicated an improvement in children’s literacy and numeracy skills across all activity locations, as reflected in higher posttest scores compared to pretest results. In addition, the program contributed to increased learning motivation and the development of positive learning habits outside school hours. It can be concluded that a community-based learning center serves as an effective, inclusive, and potentially sustainable non-formal education model to support the enhancement of children’s literacy and numeracy skills in community environments.